(untitled) (Economics and region, 2019)
The purpose of the article is to analyze the peculiarities, constituents, threats of information security of Ukraine and the development of perspective mechanisms for ensuring the information security system. The groups of information and technological threats, including information weapons, information crime, information terrorism, information manipulation, were considered. The main threats to the information security of a person, state and society are analyzed and preventive measures are proposed.